Hands-On Test Management with Jira : End-To-end Test Management with Zephyr, SynapseRT, and Jenkins in Jira. - Atar, Afsana (Packt Publishing Ltd, 2019)
This book will provide a practical understanding of the test management process with Jira. We'll start with the basic concepts taking you through the details of the software testing process followed by the organization of test artifacts in Jira. The book later explores and contrasts between the three most popular Jira plugins Zephyr, Test ...